Japan-China Strategic Alliances: The Effect of National Culture on the Evolutional Path - Magari, Taemi (2011)
In a globalising economy the number of cross-cultural strategic alliances is increasing and the large number of enterprises is entering China by using the form of strategic alliances. However, the failure rate of strategic alliance is high because process and outcome discrepancies emerge as collaboration unfolds. Although there are some reasons which generate those discrepancies, in recent decades, the affect of national culture on discrepancies has been paid attention. In the past research, however, those researches often conducted in culturally far distance countries and there is still little research on cross-cultural strategic alliances within Asian societies. Among Asian countries, especially Japan-China relationship is significant and it has a significant impact on the world economy. The objective of this dissertation is to analyze the affect of national culture on dynamic evolutional path of Japan-China strategic alliances. The dissertation begins by outlining the relationship between culture and cross-cultural alliances, and cultural characteristic of each country is briefly described. Secondly, I show the relevance of theory in terms of cross-cultural strategic alliances and cultural influence on its evolutional path analysing In-depth interview were conducted to analyze this research question. Lastly, this dissertation concludes by explaining the national cultural influence on Japan-China strategic alliances based on Hofstede’s cultural dimension, value orientation and Kumar and Nti’s alliance framework.